2015
DOI: 10.1186/s12889-015-2554-z
|View full text |Cite
|
Sign up to set email alerts
|

Burden attributable to Cardiometabolic Diseases in Zimbabwe: a retrospective cross-sectional study of national mortality data

Abstract: BackgroundCardiometabolic diseases (CMDs) are an important cause of mortality worldwide and the burden associated with them is increasing in Sub-Saharan Africa. The tracking of mortality helps support evidence based health policy and priority setting. Given the growing prevalence of non-communicable diseases in Zimbabwe, a study was designed to determine the mortality attributable to CMDs in Zimbabwe.MethodsThe study design was a retrospective cross-sectional analysis of national mortality from 1996 to 2007, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…15 Zimbabwe is also facing an increasing burden from NCDs. 16 Cerebrovascular disease is one of the leading causes of disability-adjusted life years. 17 Given the increasing burden of chronic diseases in Zimbabwe, 16 a focus on preventive care to avert high treatment costs of NCDs and a more balanced budget with more funds provided for preventive services could help avoid high OOP and CHE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Zimbabwe is also facing an increasing burden from NCDs. 16 Cerebrovascular disease is one of the leading causes of disability-adjusted life years. 17 Given the increasing burden of chronic diseases in Zimbabwe, 16 a focus on preventive care to avert high treatment costs of NCDs and a more balanced budget with more funds provided for preventive services could help avoid high OOP and CHE.…”
Section: Discussionmentioning
confidence: 99%
“…16 Cerebrovascular disease is one of the leading causes of disability-adjusted life years. 17 Given the increasing burden of chronic diseases in Zimbabwe, 16 a focus on preventive care to avert high treatment costs of NCDs and a more balanced budget with more funds provided for preventive services could help avoid high OOP and CHE. 18 This study also found that OOP spending plays a significant role in financing the health system in Zimbabwe.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB), another air-borne disease, is highly prevalent in Zimbabwe [ 12 ], with healthcare workers at elevated risk compared to the general population [ 13 ]. Zimbabweans have a high burden of chronic disease, much of which is undiagnosed, which likely affects healthcare workers to a similar extent to the rest of the population [ 14 ]. Such diseases include HIV, with an adult prevalence estimated at 12.7% [ 15 ], and non-communicable diseases such as hypertension and diabetes [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiometabolic disease is becoming progressively widespread in sub-Saharan African (SSA) nations [6], with the prevalence fluctuating from zero to about fifty percent depending on the inhabitant's location [7]. Data from some SSA countries have revealed a high mortality rate due to CMD, ranging from 17% in Zambia, Mozambique, and Zimbabwe to 36% in Cameroon [8]. The incidence of CMD in SSA could be understood to be motivated by substituting the usual African lifestyle for a Westernised one [9].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of CMD in SSA could be understood to be motivated by substituting the usual African lifestyle for a Westernised one [9]. Reasons for lifestyle change have been attributed to technological advancement, speedy urbanization, a drop in work-related physical activity, increased ingestion of nutrition that is plentiful in sugar, saturated fats, and salt/processed foods [8,9].…”
Section: Introductionmentioning
confidence: 99%